Pengaruh Edukasi Kesehatan Mental Terhadap Pengetahuan Remaja Dalam Pencegahan Bullying Berdasarkan Teori Behavioristik - A. Sri Ulfi Nofriati (Journal of Pubnursing Sciences, 2024)
Adolescence is a period that is vulnerable to experiencing negative behavior in friendships, especially at school. One of the bad behaviors that often occurs during adolescence is bullying. Bullying is a violent activity that has a negative impact, especially on mental health. To overcome the problem of bullying among teenagers, education is needed about the impact of bullying on mental health, using a behaviorist theory approach. Therefore, this research aims to determine the effect of mental health education on teenagers' knowledge of preventing bullying using a behaviorist theory approach. This research uses quantitative methods with a quasi-experimental approach and a one-group pretest-posttest design. The results of this study show that there is a significant influence of mental health educational interventions on teenagers' knowledge of preventing bullying.